Arthur babysits: an Arhtur adventure - Brown, Marc Tolon (Canada : Little Brown & Company, 1992)
Arhtur's experience babysitting for the terrible Tibble twin is a challenging as he expected, but he finally gets control by telling them a spooky story.
Keywords: Animals -- Fiction; Babysitters -- Fiction